Optimizing the Service Profit Chain Model by Enhancing Job Satisfaction to Improve Customer Oriented Employee Performance at PDAM Kota Balikpapan - Supriadi; Etty Soesilowati; Inayati Nuraini Dwiputri (PT. Maju Malaqbi Makkarana, 2026)
Clean water services are a basic need for the community, so optimizing the performance of regional drinking water companies (PDAM) is crucial to improve customer satisfaction. However, the main challenge faced by PDAM Balikpapan City is low customer satisfaction due to suboptimal service quality, which is largely influenced by employee performance. This study aims to analyze the effect of internal service quality on employee job satisfaction and customer-oriented performance, and to examine the mediating role of job satisfaction at PDAM Perumda Tirta Manuntung in Balikpapan City. This study is motivated by the importance of improving the quality of public services in the clean water utility sector, which requires organizations to be able to create an effective internal service system to support the quality of services provided to the community. This study uses an explanatory approach. Quantitative data were collected through questionnaires distributed to 196 employees, selected using the Slovin formula, while qualitative data were obtained through in-depth interviews and field observations. Data analysis used Structural Equation Modeling–Partial Least Squares (SEM-PLS) to examine the relationship between variables. The results show that internal service quality has a positive and significant influence on employee job satisfaction and customer-oriented performance. Job satisfaction was also found to have a positive and significant influence on customer-oriented employee performance. Furthermore, job satisfaction mediated the relationship between internal service quality and customer-oriented employee performance. These findings strengthen the relevance of the Service-Profit Chain Model in the context of public service organizations, particularly regional water utilities. This study provides theoretical contributions through the development of the Service-Profit Chain Model in the public utility sector, as well as practical contributions for PDAM management in formulating strategies to continuously improve internal service quality, job satisfaction, and customer service quality.